BODIPY-Based Ratiometric Fluorescent Probe for Sensing Peroxynitrite in Inflammatory Cells and Tissues - Qian Wu; Ziwei Hu; Guoyang Zhang; Yulong Jin; Zhuo Wang (Biosensors)
Peroxynitrite (ONOO−) plays an important role in many physiological and pathological processes. Excessive ONOO− in cells leads to oxidative stress and inflammation. However, precise monitoring of ONOO− levels in specific organelles (e.g., mitochondria) is still lacking and urgently needed. Herein, we rationally designed a mitochondria-targeted ratiometric fluorescent probe, MOBDP-I, for imaging of ONOO− in the mitochondria of inflammatory cells and model mice. This probe, MOBDP-I, was synthesized by conjugating a BODIPY fluorophore to a mitochondria-targeting moiety–indole-salt group by a carbon–carbon double bond (C=C). In the presence of ONOO−, the C=C bond between the BODIPY backbone and the indole-salt group was oxidized and broken, leading to an 18-fold enhancement of fluorescence at 510 nm, along with a significant fluorescence decrease at 596 nm. The ratiometric response property bestowed the probe with advantages in the precise quantification of ONOO− in cells, thus allowing estimation of the extent of inflammation in living cells and mouse models of rheumatoid arthritis, peritonitis, and brain inflammation. MOBDP-I could act as an effective molecular tool to study the relationship between ONOO− and the occurrence and development of inflammatory diseases.